Alternating Stacked Graphene-Conducting Polymer Compact Films with Ultrahigh Areal and Volumetric Capacitances for High-Energy Micro-Supercapacitors - Wu, Zhong-Shuai; Parvez, Khaled; Li, Shuang; Yang, Sheng; Liu, Zhaoyang; Liu, Shaohua; Feng, Xinliang; Muellen, Klaus (Advanced Materials, 2015)
Graphene-based compact nanohybrid films made by alternate deposition of electrochemically exfoliated graphene and mesoporous graphene-conducting polymer nanosheets are constructed for high-energy micro-supercapacitors. They are shown to have a landmark areal capacitance of 368 mF cm-2 and volumetric capacitance of 736 F cm-3.
CRIS-Team Scopus Importer:2023-03-20
Keywords: compact films; energy storage; graphene; micro-supercapacitors; polymer nanosheets